Aging and differentiation in yeast populations: elders with different properties and functions. Issue 1 (25th October 2013) - Palková, Zdena; Wilkinson, Derek; Váchová, Libuše
Abstract Over the past decade, it has become evident that similarly to cells forming metazoan tissues, yeast cells have the ability to differentiate and form specialized cell types. Examples of yeast cellular differentiation have been identified both in yeast liquid cultures and within multicellular structures occupying solid surfaces. Most current knowledge on different cell types comes from studies of the spatiotemporal internal architecture of colonies developing on various media. With a few exceptions, yeast cell differentiation often concerns nongrowing, stationary‐phase cells and leads to the formation of cell subpopulations differing in stress resistance, cell metabolism, respiration, ROS production, and others. These differences can affect longevity of particular subpopulations. In contrast to liquid cultures, where various cell types are dispersed within stationary‐phase populations, cellular differentiation depends on the specific position of particular cells within multicellular colonies. Differentiated colonies, thus, resemble primitive multicellular organisms, in which the gradients of certain compounds and the position of cells within the structure affect cellular differentiation. In this review, we summarize and compare the properties of diverse types of differentiated chronologically aging yeast cells that have been identified in colonies growing on different media, as well as of those found in liquid cultures.